The education of at-risk children: the challenges ahead - Md Nor, Sharifah (Bahagian Komunikasi Korporat, Universiti Putra Malaysia, 2004)
There is a significant number of students in our schools who are at-risk of school failure. These at-risk learners are generally low achievers, demonstrating low engagement to learning and to other activities of the school. They may also have behavioural problems. Generally they have certain characteristics that render them unable to cope with the demands of the school. These low achievers may either drop out of school early or are still in school until they complete eleven years of schooling. What ever path they take they pose a number of challenges to us, namely how to prevent them from dropping out early, equally important, how we can make their stay in school meaningful and productive so that they can achieve their potentials to the fullest. The paper attempts to identify school factors affecting the learning of at-risk students who are generally placed in the lowest streams and to present an analysis of their academic achievement, and socio-psychologicallearning environment. It attempts to highlight the challenges faced by the schools in meeting the needs of these at-risk children, such as early intervention, learning environment, teaching and learning approaches, support services, teachers' needs and skills. Promising programs and efforts undertaken by other countries will also be discussed in order to learn from their experiences. It is indeed a challenge to transform schools, which generally serve some students better than others to be equally sensitive to the needs of all students. It is also equally challenging to transform at-risk students into happy individuals fully engaged in learning and to become productive and valuable members of the society.